The Contribution of Form Repetition to Listeners' Expectation of Givenness in Online Reference Resolution. Issue 9 (21st October 2021) - Lee, Eun-Kyung; Lam, Tuan Q.; Watson, Duane G.
ABSTRACT: Although it is clear that unaccented referring expressions are associated with given information in a discourse, it is less clear what aspects of givenness are relevant. We examine whether listeners' expectation of givenness depends on repetition of a referring expression or on contextual evocation of a referent. The results from two visual world eye-tracking experiments suggest that for interpretation, listeners associated reduced prominence with a repeated referring expression. Listeners expect previously evoked referents to be candidates for reduced referring expressions only when they are referred to with the exact same referential form. The data also suggest that when referents are referred to with different referential forms across utterances, accenting facilitates linking those forms for co-reference.